Pacific finance sector brief Kiribati. (Metro Manila, Philippines Asian Development Bank, 2019)
The countrys finance sector is limited in size and scope of operations. ANZ Kiribati is the only bank while there are two public financial institutions: the Development Bank of Kiribati and the Kiribati Provident Fund. These are complemented by the state-owned Kiribati Insurance Corporation and a few small credit unions. Private sector credit is expanding, aided by the two public financial institutions. A key challenge is the scarcity of financial data, which greatly hinders analysis of the sector to inform targeted interventions. The International Monetary Fund recommends addressing this issue as a priority for the country.
Keywords: Finance -- Kiribati; Industrial policy; Electronic books